Pemanfaatan Minyak Jelantah menjadi Sabun Batang Cuci Piring di Desa Gondang Kabupaten Wonogiri - Alawia, Mutia Tsalitsa; Muslikah; Zakiyatul Muna, Zahro; Vega Savela, Sovia; Alan Gumara, Victor (Institut Agama Islam Negeri Ponorogo, 2023)
Waste cooking oil is a relatively large source of waste in Gondang Village because it results from dated houses and waste from MSMEs. Based on these problems, this community service aims to provide an understanding of the dangers of waste cooking oil and reprocessing it into bar soap with a zero waste concept through training with Famili Welfare Programme (PKK) women and MSME people. The approach used was Asset Based Community Development (ABCD) with the hope that after this training, the Gondang village community can process waste cooking oil into bar soap and have a higher economic value to increase their source of income as wel.